Greenhouse Gas Emissions and Management Practices that Affect Emissions in US Rice Systems. Issue 3 (1st May 2018) - Linquist, Bruce A.; Marcos, Mathias; Adviento‐Borbe, M. Arlene; Anders, Merle; Harrell, Dustin; Linscombe, Steve; Reba, Michele L.; Runkle, Benjamin R. K.; Tarpley, Lee; Thomson, Allison
Abstract : Previous reviews have quantified factors affecting greenhouse gas (GHG) emissions from Asian rice ( Oryza sativa L.) systems, but not from rice systems typical for the United States, which often vary considerably particularly in practices (i.e., water and carbon management) that affect emissions. Using meta‐analytic and regression approaches, existing data from the United States were examined to quantify GHG emissions and major practices affecting emissions. Due to different production practices, major rice production regions were defined as the mid‐South (Arkansas, Texas, Louisiana, Mississippi, and Missouri) and California, with emissions being evaluated separately. Average growing season CH4 emissions for the mid‐South and California were 194 (95% confidence interval [CI] = 129–260) and 218 kg CH4 ha −1 season −1 (95% CI = 153–284), respectively. Growing season N2 O emissions were similar between regions (0.14 kg N2 O ha −1 season −1 ). Ratoon cropping (allowing an additional harvestable crop to grow from stubble after the initial harvest), common along the Gulf Coast of the mid‐South, had average CH4 emissions of 540 kg CH4 ha −1 season −1 (95% CI = 465–614). Water and residue management practices such as alternate wetting and drying, and stand establishment method (water vs. dry seeding), and the amount of residue from the previous crop had the largest effect on growing season CH4 emissions. However, soil texture, sulfate additions, and cultivar selection also affected growing season CH4 emissions. This analysis can be used for the development of tools to estimate and mitigate GHG emissions from US rice systems and other similarly mechanized systems in temperate regions. Core Ideas: Emissions of CH4 and N2 O were quantified for US rice systems using a meta‐analysis. Emissions were determined for both the growing and fallow seasons. We assessed the major management practices affecting emissions. Analysis can be used to develop a tool for quantifying emissions from rice fields.